Dynamics of anxiety of participants of united forces operation - Boiarska, Zoryna; Pinchuk, Roman (ScienceRise: Biological Science, 2018)
The purpose of the work - to investigate features of a psychological state of the participants in the united forces operation that were in the east of our state on the second line of defense for four months. Materials and research methods. Questionnaires of fighters-contractors according to the methods: "Scale of reactive and personal anxiety Ch.D. Spielberger - Yu.L. Khanina "and the Beck Depression Inventory (BDI) questionnaire. The study was conducted in the first days after arriving at the location site, two months in the zone of the united forces operation and two weeks after returning from the war zone. The study was conducted on the basis of 177 separate radar platoon (Lisichansk, Lugansk region) with combatants-volunteers from April to August 2018. Simulation Results. As a result of the study, there were established a predominantly moderate level of reactive and personal anxiety and the absence of signs of depression at the beginning of the assignment and during the stay in the area of the operation. There was an increase in the level of anxiety and the appearance of signs of depression after returning from the combat zone. The analysis of the main problems of the participants of the operation of the combined forces arising from the return to the conditions of peaceful life (violation of the rights to social guarantees, bureaucratic problems when applying for benefits) has been carried out. Conclusions. Thus, in the first days of arrival in the combat zone, the combatants are dominated by the average level of reactive and personal anxiety, and there are no signs of depression. After two months of performing combat missions, the level of reactive and situational anxiety among combatants remains within the average indicators, the participants of the study have no signs of depression, which allows to conclude that a high adaptive level is achieved. Two weeks after returning from the combat zone, most combatants increase the level of reactive anxiety and show signs of mild depression. The prospect of further research is seen in the development of effective methods for the physical and psychological rehabilitation of combatants in order to increase their adaptive capabilities upon returning from the environment